MAXIMUM HEART RATE MEASURED VERSUS ESTIMATED BY DIFFERENT EQUATIONS DURING THE CARDIOPULMONARY EXERCISE TEST IN OBESE ADOLESCENTS - Heinzmann-Filho, João Paulo (Rev Paul Pediatr, 2018)
OBJECTIVE: To compare the values of measured maximum heart rate (HRmax) and maximum heart rate estimated by different equations during the cardiopulmonary exercise test (CPET) in obese adolescents. METHODS: This is a cross-sectional study. Adolescents aged between 15 and 18 years old, with obesity (BMI Z-score>2.0) were included. Demographic and anthropometric data were collected, followed by CPET, recording HRmax. The highest heart rate reached at peak exercise was considered as HRmax. The comparison between measured and estimated HRmax values was performed using four previous equations. Descriptive statistics and the ANOVA test (Bonferroni post-test) were used. RESULTS: Fifty-nine obese adolescents were included, 44% of them male. The mean age was 16.8±1.2 years old and the BMI (Z-score) was 3.0±0.7. At peak exercise, the mean HRmax (bpm) was 190.0±9.2, the respiratory coefficient was 1.2±0.1, and the VO(2)max (mL/kg/min) was 26.9±4.5. When comparing the measured values of HRmax with those estimated by the different formulas, the equations “220-age”, “208-0.7 x age” and “207-0.7 x age” were shown to overestimate (p<0.001) the measured HRmax results in obese adolescents. Only the “200-0.48 x age” equation presented similar results (p=0.103) with the values measured in the CPET. CONCLUSIONS: The findings of the present study demonstrate that the equation “200-0.48 x age” seems to be more adequate to estimate HRmax in obese adolescents.